Regulation and use of the extracellular matrix by Trypanosoma cruzi during early infection - Nde, Pius N.; Lima, Maria F.; Johnson, Candice A.; Pratap, Siddharth; Villalta, Fernando (Frontiers in Immunology, 2012)
Chagas disease, which was once thought to be confined to endemic regions of Latin America, has now gone global becoming a new worldwide challenge. For more than a century since its discovery, it has remained neglected with no effective drugs or vaccines. The mechanisms by which Trypanosoma cruzi regulates and uses the extracellular matrix to invade cells and cause disease are just beginning to be understood. Here we critically review and discuss the regulation of the extracellular matrix (ECM) interactome by T. cruzi, the use of the ECM by T. cruzi and analyze the molecular ECM/T. cruzi interphase during the early process of infection. It has been shown that invasive trypomastigote forms of T. cruzi use and modulate components of the ECM during the initial process of infection. Infective trypomastigotes up-regulate the expression of laminin γ-1 (LAMC1) and thrombospondin (THBS1) to facilitate the recruitment of trypomastigotes to enhance cellular infection. Silencing the expression of LAMC1 and THBS1 by stable RNAi dramatically reduces trypanosome infection. T. cruzi gp83, a ligand that mediates the attachment of trypanosomes to cells to initiate infection, up-regulates LAMC1 expression to enhance cellular infection. Infective trypomastigotes use Tc85 to interact with laminin, p45 mucin to interact with LAMC1 through galectin-3 (LGALS3), a human lectin, and calreticulin (TcCRT) to interact with TSB1 to enhance cellular infection. Silencing the expression of LGALS3 also reduces cellular infection. Despite the role of the ECM in T. cruzi infection, almost nothing is known about the ECM interactome networks operating in the process of T. cruzi infection and its ligands. Here, we present the first elucidation of the human ECM interactome network regulated by T. cruzi and its gp83 ligand that facilitates cellular infection. The elucidation of the human ECM interactome regulated by T. cruzi and the dissection of the molecular ECM/T. cruzi interphase using systems biology